Box Behnken optimization of cubosomes for enhancing the anticancer activity of metformin: Design, characterization, and in-vitro cell proliferation assay on MDA-MB-231 breast and LOVO colon cancer cell lines - Randa Mohammed Zaki; Layla A. Alkharashi; Omnia M. Sarhan; Alanood S. Almurshedi; Basmah Nasser Aldosari; Mayada Said (Elsevier, 2023)
This study aimed to formulate and statistically optimize cubosomal formulations of metformin (MTF) to enhance its breast anticancer activity. A Box Behnken design was employed using Design-Expert® software. The formulation variables were glyceryl monooleate concentration (GMO) w/w%, Pluronic F-127 concentration (PF127) w/w% and Tween 80 concentration w/w% whereas Entrapment efficiency (EE%), Vesicles' size (VS) and Zeta potential (ZP) were set as the dependent responses. The design expert software was used to perform the process of optimization numerically. X ray diffraction (XRD), Transmission electron microscope (TEM), in-vitro release study, short-term stability study, and in in-vitro cell proliferation assay on the MDA-MB-231 breast cancer and LOVO cancer cell lines were used to validate the optimized cubosomal formulation. The optimized formulation had a composition of 4.35616 (w/w%) GMO, 5 (w/w%) PF127 and 7.444E-6 (w/w%) Tween 80 with a desirability of 0.733. The predicted values for EE%, VS and ZP were 78.0592%, 307.273 nm and − 26.8275 mV, respectively. The validation process carried out on the optimized formula revealed that there were less than a 5% variance from the predicted responses. The XRD thermograms showed that MTF was encapsulated inside the cubosomal vesicles. TEM images of the optimized MTF cubosomal formulation showed spherical non-aggregated nanovesicles. Moreover, it revealed a sustained release profile of MTF in comparison to the MTF solution. Stability studies indicated that optimum cubosomal formulation was stable for thirty days. Cytotoxicity of the optimized cubosomal formulation was enhanced on the MDA-MB-231 breast and LOVO cancer cell lines compared to MTF solution even at lower concentrations. However, it showed superior cytotoxic effect on breast cancer cell line. So, cubosomes could be considered a promising carrier of MTF to treat breast and colon cancers.